Current relevance of hypoxia in head and neck cancer - Bredell, Marius G. (Oncotarget, 2016)
Head and Neck cancer (HNC) is a complex mix of cancers and one of the more common cancers with a relatively poor prognosis. One of the factors that may assist us in predicting survival and allow us to adjust our treatment strategies is the presence of tumor hypoxia. In this overview we aim to evaluate the current evidence and potential clinical relevance of tumor hypoxia in head and neck cancer according to an extensive search of current literature. An abundance of evidence and often contradictory evidence is found in the literature. Even the contradictory evidence and comparisons are difficult to judge as criteria and methodologies differ greatly, furthermore few prospective observational studies exist for verification of the pre-clinical studies. Despite these discrepancies there is clear evidence of associations between prognosis and poor tumor oxygenation biomarkers such as HIF-1α, GLUT-1 and lactate, though these associations are not exclusive. The use of genetic markers is expanding and will probably lead to significantly more and complex evidence. The lack of oxygenation in head and neck tumors is of paramount importance for the prediction of treatment outcomes and prognosis. Despite the wide array of conflicting evidence, the drive towards non-invasive prediction of tumor hypoxia should continue.